Satisfaction Dimensional Analysis of Mothers with Toddlers Regarding Visits to Integrated Health Posts (Posyandu) During the New Normal Period - Zahnia, Siti; -, Adinda (Jurnal Manajemen Informasi Kesehatan (Health Information Management), 2024)
Posyandu provides easy access to basic health services for the community, particularly to reduce maternal and infant mortality rates (MMR) and infant mortality rates (IMR). However, since the COVID-19 pandemic, the number of toddler visits to Posyandu has decreased. The average percentage of toddlers weighed in Lampung Province is 67.5%, and the D/S indicator in Metro City is 72.6%, still below the provincial target of 80%. The purpose of this study is to analyze the satisfaction dimensions of mothers with toddlers regarding visits to Posyandu during the new normal period in the Mulyojati Community Health Center (Puskesmas) in Metro City in 2022. This study was quantitative with a cross-sectional design. The study population was 660 and the sample size was 242. The sampling method used was non-random sampling, purposive sampling, and proportional sampling. Analysis used chi-square and logistic regression. The study found a correlation between satisfaction with the direct evidence dimension (p-value 0.000 OR=2.9), reliability (p-value 0.006 OR=2.1), responsiveness (p-value 0.000 OR=2.8), confidence (p-value 0.000 OR=3.9), and empathy (p-value 0.000 OR=3.3) and visits by mothers with toddlers to integrated health posts (Posyandu) during the new normal period. The assurance dimension was the most dominant variable influencing visits by mothers with toddlers to integrated health posts (Posyandu) during the new normal period (OR=3.3). Local governments should improve the capacity of Posyandu cadres in interpersonal interactions/effective communication with their target audiences and improve their competency in serving infants and toddlers. Support cadres in improving their knowledge and skills by accessing specialized reading materials and holding jamborees for Posyandu cadres.